Weight of Different Intraocular Lenses: Evaluation of Toricity, Focality, Design, and Material. (21st April 2021) - López-Vázquez, Ángel; Contreras, Inés; Martin-Prieto, Sergio; López-Castro, Ángel
Abstract : Purpose . To evaluate the weight of intraocular lenses (IOLs) depending on their material, dioptric power, toricity, focality, and haptic design. Methods . Twenty-eight different IOL models from nine different medical companies (a total of 38 IOLs) and 1 capsular tension ring (CTR) were evaluated. IOLs were weighed using a precision scale, in hydrated conditions, as an approximation to their intraocular status. Results . Hydrophilic IOLs were heavier than hydrophobic lenses (p < 0.001 ). Regarding toricity, no statistical differences were found comparing toric to non-toric models (p = 0.1 ). Likewise, no differences were found between multifocal IOLs and monofocal IOLs (p = 0.19 ). Dioptric power did not affect IOL weight: IOLs of <15DP had similar weights to those of ≥15D and IOLs of ≥24D had similar weights to those of <24 D (p = 0.86 and p = 0.59, respectively). Plate-design IOLs were significantly heavier than 1-piece C-loop (p < 0.001 ), 3-piece C-loop (p < 0.001 ), and 4-haptic lenses (p = 0.001 ). Conclusions . Of the characteristics analyzed that might influence IOL weight, lenses with hydrophilic material and plate-haptic design were found to be heavier. Toricity, focality, and dioptric power had no influence on IOL weight.